The Reconstruction of the Anterior Cruciate Ligament on the Background of Knee Osteoarthritis - Golovakha, M. L.; Orljanski, W.; Benedetto, K. P.; Головаха, Максим Леонідович (My University, 2019)
Instability of the knee joint due to the injury of the anterior cruciate ligament is the issue which constantly draws attention of orthopedists. There is a constant development of methods of the reconstruction of the anterior cruciate ligament which, in its turn, primarily connected with a more accurate positioning of the graft attachment. There is a polemic in progress dedicated to the choice of the graft for the reconstruction of the anterior cruciate ligament and the ways of its attachment [1-5]. However, the instability backsets occur in 5-25 % of the cases and the level of patients returning to sport after the plastic reconstruction of the anterior cruciate ligament is from 60 to 80 % [1-8]. There is a special group which consists of the patients with the injury of the anterior cruciate ligament who have cartilage lesion or ongoing osteoarthritis of the knee. The results of the treatment of these patients are poor, since in most cases they are recommended to follow the conservative treatment.